Pengaruh Penerapan Model Pembelajaran Kooperatif TGT pada Pembelajaran IPAS terhadap Kemampuan Berpikir Kritis Siswa Kelas IV SD Negeri 01 Dagen Karanganyar Tahun Ajaran 2024/2025 - Kaneshia Istiqomah Azzahra; Oktiana Handini; Mukhlis Mustofa (Lembaga Pengembangan Kinerja Dosen, 2025)
This research was conducted on fourth-grade students of SD Negeri 01 Dagen Karanganyar with the aim of identifying the improvement of critical thinking skills in IPAS learning by applying the Cooperative Learning Model of the Teams Games Tournament (TGT) type during the 2024/2025 academic year. The study involved 25 students, consisting of 16 male students and 9 female students. This research belongs to quantitative research with a One-Group Pre-Test Post-Test Design. The research procedure began with administering a tryout test to determine the number of valid items to be used. The validity test results showed that 20 items met the validity criteria during the tryout. Data analysis was conducted using the One-Sample Shapiro-Wilk test for normality and the Paired Sample T-Test for hypothesis testing. Based on the analysis, the results showed a significance value of < 0.000 with a significance probability of < 0.05. Therefore, the findings are consistent with the hypothesis, namely: “There is an effect of using the Teams Games Tournament (TGT) Learning Model in IPAS learning on the critical thinking skills of fourth-grade students at SD Negeri 01 Dagen Karanganyar in the 2024/2025 academic year.” This indicates that the TGT model can enhance students’ ability to think critically, helping them develop essential skills in problem-solving, analysis, and decision-making, which are crucial for their academic success and future learning processes.